(untitled) (Semiárida, 2024)
The Central Plateau of Santa Cruz was productively occupied with sheep in the late 1800s and early 1900s. The initial productivity of the natural pasture, supporting high instantaneous loads, led to not taking into account the impact that year-round grazing brings with it and that would lead, in later years, to the exhaustion of that resource and generate an acute process of desertification, which would end up seriously compromising the sustainability of extensive sheep production. A brief review of the characteristics of the natural environment of the Meseta (soil, vegetation, water and climate) is carried out, and within this ecological area, a territorial cut was made in the Department of Magallanes (considering this territorial division as a sample of the diversity of environments that the Meseta contains), where a polygon was defined in which to concentrate the observation and intervention efforts, oriented to weigh the problem of desertification and the centrality acquired by the guanaco, a native herbivore, considered by producers as one of the central factors of the current critical situation of extensive sheep farming. Using the method of the pentagon of capitals we can address key dimensions and their interrelation in a specific observation area and analyze the possibilities of carrying out sustainable production.